Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan - Rizalma Laela Ardhana; Suhendro Suhendro; Sari Kuriniati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to test and analyze the impact of leverage, liquidity, capital structure, and company size on financial performance. The data used comes from the financial statements of manufacturing business entities in the consumer goods industry sector on the Indonesia Stock Exchange (IDX) in the 2019-2022 period. The study population involved business entities in the consumer goods industry sector listed on the IDX during that period. The sample was selected using purposive sampling method, and consisted of 35 business entities. The data were analyzed by multiple linear regression processed using SPSS version 21. The results showed that the leverage variable has an influence on financial performance, capital structure has an influence on financial performance, and company size also has an influence on financial performance. However, there is no relationship between liquidity and financial performance. For future research, it is recommended that the population coverage be expanded to include all business entities listed on the IDX, the research period be extended to obtain a more comprehensive generalization, and add additional variables that have not been considered in this study that may affect financial performance. Keywords: Financial Performance, Leverage, Liquidity